Genotypic Variability, Correlation and Path Analysis among Yield Components in Kenaf Mutants under Tropical Conditions - Md Al-Mamun, .; Rafii, Mohd Y.; Oladosu, Yusuff; Misran, Azizah; Berahim, Zulkarami; Md Mahmudul Hasan Khan, .; Arolu, Fatai (Taylor & Francis, 2022)
Correlation and path coefficient analysis aid in developing breeding strategies aimed at increasing yield traits through selection by providing a better understanding of the relationship. This study was conducted on yield and yield-related traits to determine their direct and indirect effects among thirty-one kenaf mutant lines to identify selection criteria for higher fiber yield. The analysis of variance showed significant differences for all the characters studied except for top diameter, where non-significant differences were observed for genotype and genotype by season interaction. The dry fiber weight significantly correlated with seven traits at the phenotypic and genotypic levels. Hence, selection based on these traits is effective for increasing kenaf fiber yield. Path coefficient analysis revealed that fresh stem weight without leaves and pod (0.223) had the maximum contribution to fiber yield per plant, followed by plant height (0.202). Fresh stem weight without leaves and pod (0.252) exhibited the maximum positive direct effect on fiber yield followed by middle diameter (0.226) and plant height (0.186). For the development of kenaf varieties with acceptable yield, effective selection would consider plant height, middle diameter, core diameter, dry stick weight, fresh stem weight with leaves and pod, and fresh stem weight without leaves and pod.